Religious life for women from the twelfth century to the middle of the fourteenth century with special reference to the English foundations of the Order of Fontevraud - Kerr, B; B. M. Kerr (1995)
﻿ The Order of Fontevraud, founded in 1100 by the hermit/preacher Robert of Arbrisssel was the only twelfth-century women's order incorporating into its structure a group of chaplains and lay brothers whose specific role was to serve the nuns. This thesis examines the origins of the order and demonstrates that the English foundations were a stage in its development, closely linked to its Angevin connections. Each of the two houses established in England c.l 150 was founded and patronised by supporters of Henry Plantagenet. Westwood, founded by the de Say family, lesser barons from Herefordshire, received a modest endowment. Nuneaton, founded by the magnate Robert, earl of Leicester, was richly endowed. Twenty years later Henry II expelled the Benedictine community from Amesbury replacing it with a group from Fontevraud, thus founding the third house. A fourth, Grovebury, is not treated; it was never a foundation for women. I have studied the process of endowment and shown that the wealth and status of the founder in no small measure determined the future prosperity of the foundation. The internal organisation of the Fontevraud houses has been explored, in particular the balance between local autonomy and dependence on the mother house. As well, I have examined recruitment and shown that this, too, reflected on the circumstances of foundation. My main focus has been on the economy of these three houses, their income and expenditure and the exploitation of their assets. The nuns are seen as a group of women who were dynamic and creative in managing their affairs. This has not precluded an investigation into the spiritual, and in particular, the liturgical dimension of life in the English foundations. Fundamentally the Order of Fontevraud is presented as an opportunity for noble women of England in the twelfth and thirteenth centuries to live religious life in a new order, one renowned for its strict interpretation of the Rule of St Benedict and for the prayerfumess of its members, and one in which women were manifestly in control of their own destinies.